Combine Effect of Myofascial Release and Ocular Muscle Exercise for Eye Strain Headache in University Students: Randomized Controlled Trial - Maqsood, Sonia; Khan, Hafiz Yaseen; Shabi ul Hassan; Gul, Neelo; Khan, Noman; Ahmed, Shamshaid; Rehman, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Eyestrain headache commonly found in myopia patients, caused by exaggerated workload or strained due to the prolong activities which required highly focusing, such as reading and using digital gadgets. Symptom includes peri-orbital pain, forehead heaviness, fuzzy or cloudy vision, and dry eyes. Objective: To determine the combine effect of myofascial release in eyestrain headache participants using ocular muscle exercises and to find the length of sternocleidomastoid and upper trapizus muscle in myopic individual after the treatment. Methods: An experimental study was conducted at Abasyn University, Peshawar, followed by the inclusion criteria. A total of 36 participants between 20 to 30 years of age were included. We equally divided the participants into two groups A (experimental) and group B (control). Out of 36 participants 8 (44.4%) were male and 14 (77.8%) were female in the experimental group while 10 (55.6%) male and 8(22.2%) were female in the control groups, having mild to moderate myopia, unilateral or bilateral headaches, and peri-orbital pain. The study was carried out for three weeks periods, with three sessions each week of the treatment. Computer vision syndrome questionnaire was filled before and after completing their session. For data analyses SPSS version 25 was used. Results: The mean age in the experimental group were 1.38 years while control group were 1.44 years respectively. Their mean visual acuity in group A 9(50.0%) and group B 15(83.3%) was mild while in group A 9(50.0%) and groups B 3(16.7%) were moderately affected. A significant reduction was noticed in eyestrain headache individuals by using myofascial release techniques on the neck muscles (sternocleidomastoid and upper trapezius) and muscles lengthening were significantly increased after an exercise which enhances muscle flexibility and elasticity. A mixed ANOVA test was performed between the groups. Conclusion: The study’s findings indicate that myofascial release therapy and ocular muscle training significantly reduced headaches caused by eyestrain and increased the length of the neck’s sternocleidomastoid and upper trapezius muscles.